Governmental origin: why NTBFs grow in a transitional economy. Issue 1 (1st January 2020) - Farnoodi, Sanam; Ghazinoory, Sepehr; Radfar, Reza; Tabatabaian, Seyed Habibollah
Abstract: The NTBFs have attracted growing interest from most of the transitional economies as they are seen as an important source of greater value added creation while being characterised with higher rate of return on capital. Shedding light on the growth determinants of new technology-based firms not only helps managers to accomplish organisational goals but also assists policymakers in devising effective strategies. The role of individual, organisational as well as environmental factors in the development of the new technology-based firms has been separately addressed by many researchers. The simultaneity of these factors leads to diverse configurations, each of which envisaging different growth paths for the firm. The aim of this paper is to identify the growth paths for the new technology-based firms. To this end, Some interviews were conducted with the managers of the developed new technology-based firms in Iran (as a transitional economy) and the key themes governing the growth pattern of this group of firms have been identified using the thematic analysis, while possible growth paths for these firms were established by means of qualitative comparative analysis. The designed questionnaires were distributed among 22 developed firms and 8 underdeveloped firms for the period 2013–2015 and the obtained data were analysed using the FSQCA software, which led us to the development of dominant growth path for new technology-based firms. Based on the findings of this paper and factors affecting the growth of firms, two growth paths are suggested for the new technology-based firms, of which the one with greater role for government is more likely to take place. Communication with government officials and lobbying groups in the field of science and technology as the key customer in transitional economies is critical to the corporate growth, which has been identified as a sufficient condition for this research.